Comparing outcomes of treatments with ETRANS-based electrical stimulation versus electrical phosphene stimulation in patients with accommodative dysfunction (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To investigate the influence of ocular electrical stimulation (either ETRANS-based or electrical phosphene stimulation (EPS)) on the accommodative, convergence and pupillary system in patients with accommodative dysfunction using objective computerized pupillography.Materials and Methods: Of a total of 59 low myopic children and adolescents with accommodative spasm included in the study, 39 underwent ocular electrical stimulation with the use of ETRANS apparatus, and 20 underwent EPS of the eye. The computerized pupillographer OK-2 was used to obtain images of direct response, consensual response and accommodative convergence response.Results: ETRANS-based electrical stimulation and EPS imposed a unidirectional effect on patients with accommodative dysfunction, with mean percentage improvement in uncorrected visual acuity of 33% and 49%, respectively, and 2.86 times and 4.1 times increases, respectively, in mean accommodative reserve, compared to baseline. In addition, minimum pupil area (after presentation of the stimulus for accommodative convergence), delay in pupillary contraction and active pupillary contraction time decreased by 13%, 10.7%, and 11.5%, respectively, after ETRANS-based electrical stimulation, and active pupillary contraction time decreased by 27% after EPS.
Keywords: accommodative dysfunction; low myopia; electrical stimulation; ETRANS; electrical phosphene stimulation; computerized pupillography